Protective Role of Catechin and Quercetin in Sodium Benzoate-Induced Lipid Peroxidation and the Antioxidant System in Human Erythrocytes In Vitro - Gamze Yetuk; Dilek Pandir; Hatice Bas (The Scientific World Journal)
The aim of this study was to evaluate the protective effect of catechin and quercetin in sodium benzoate- (SB-) induced oxidative stress in human erythrocytes in vitro. For this, the effects of SB (6.25, 12.5, 25, 50, and 100 μg/mL), catechin (10 μM), and quercetin (10 μM) on lipid peroxidation (LPO) and the activities of SOD, CAT, GPx, and GST were studied. Significantly higher LPO and lower activities of antioxidant enzymes were observed with the increasing concentrations of SB. Catechin or quercetin protected the erythrocytes against SB-induced toxicity only at low concentrations of SB. The presence of catechin or quercetin at 10 μM have no effect on SB-induced toxicity at high concentrations of SB (50 and 100 μg/mL). In conclusion, SB may cause oxidative stress as food additive in human erythrocytes in vitro. So, it appears that our findings provide evidence for the protection of erythrocytes from SB that could be considered for further studies.